Schwarz-Pick-type estimates for the hyperbolic derivative. (18th May 2006) - Mercer, Peter R.
Abstract : We obtain Schwarz-Pick-type estimates for the hyperbolic derivative of an analytic self-map of the unit disk inℂ .